Hypoacousis prevalence in Kaiowá and Guarani indigenous children Prevalência de hipoacusia em crianças indígenas Kaiowá e Guarani - Renata Palópoli Pícoli; Luana Carandina; Dulce Lopes Barbosa Ribas (Instituto Materno Infantil de Pernambuco, 2006)
OBJECTIVES: to determine hypoacousis prevalence in Kaiowá and Guarani indigenous children. METHODS: a cross-sectional study was performed using a sample of 126 indigenous children from zero to 59 months old from the Caarapó Indian Reserve, Mato Grosse do Sul, Brazil. Hearing ability screening was performed by measuring transient evoked otoacoustic emissions. Children with hearing impairment were retested. Confirmed cases following retest were referred to imitanciometry testing. RESULTS: during hearing ability screening, 25 (23.6%) children showed hearing impairment. Seventeen children had normal outcomes during retest and six of them confirmed hearing impairment and were referred to imitanciometry testing. Hypoacousis prevalence identified by the study reached 5.6%, 3 (2.8%) and 3 (2.8%) suggestive of conductive and sensorineural types, respectively. The last ones were referred to complementary otorhinolaryngologic assessment for diagnosis confirmation. Hearing impairment cases determined by this study were not statistically significant when related to gender and age. CONCLUSIONS: problems concerning the prevalence of hearing impairment determined in the focused population suggest the need for hearing health programs to be developed with other child health programs. OBJETIVOS: identificar a prevalência de hipoacusia em crianças indígenas Kaiowá e Guarani. MÉTODOS: estudo transversal, com uma amostra de 126 crianças indígenas de zero a 59 meses da Terra Indígena de Caarapó, em Mato Grosso do Sul, Brasil. As crianças foram submetidas ao exame das emissões otoacústicas evocadas transitórias, que serviu como triagem auditiva. O reteste foi realizado nas crianças que apresentaram resultado alterado na triagem auditiva. Os casos que, no reteste, permaneceram alterados foram encaminhados para o exame da imitanciometria. RESULTADOS: na triagem auditiva, foram identificadas 25 (23,6%) crianças com resultado alterado; dessas, 17 apresentaram resultado normal no reteste e 6 permaneceram com resultado alterado, sendo encaminhadas para imitanciometria. A prevalência de hipoacusia identificada ao final do estudo foi de 5,6%, sendo 3 (2,8%) do tipo condutiva e 3 (2,8%) do tipo neurossensorial. Estas últimas foram encaminhadas à avaliação otorrinolaringológica complementar para confirmação diagnóstica. As alterações auditivas identificadas neste estudo não apresentaram diferenças significantes quanto ao sexo e grupo etário. CONCLUSÕES: a prevalência de alteração auditiva encontrada nesta população alerta para a necessidade de implantação de programas de saúde auditiva e sua articulação com outras ações desenvolvidas na atenção à saúde infantil dos Kaiowá e Guarani.